Multi-media teacher training and HIV-related stigma among primary and secondary school teachers in Western Kenya. Issue 5 (4th May 2023) - Nyandiko, Winstone; Chory, Ashley; Baum, Aaron; Aluoch, Josephine; Ashimosi, Celestine; Scanlon, Michael; Martin, Roxanne; Wachira, Juddy; Beigon, Whitney; Munyoro, Dennis; Apondi, Edith; Vreeman, Rachel
ABSTRACT : HIV stigma is associated with delayed HIV disclosure and worse clinical outcomes for adolescents living with HIV (ALWH). Teachers critically influence school environments, but are understudied in terms of HIV stigma. We implemented a school-level, cluster-randomized trial to assess the impact of a one-day multi-media training on the knowledge, attitudes and beliefs (K/A/B) of school teachers in western Kenya. Teachers' K/A/B were evaluated at baseline and six months. Additionally, we assessed stigma with ALWH enrolled in the included schools to explore the impact of the training. Teachers (N = 311) and ALWH (N = 19) were enrolled from 10 primary and 10 secondary schools. The intervention and control groups did not significantly differ in overall stigma score (mean 1.83 vs. 1.84; adjusted difference, 0.18 [95% CI, −0.082 to 0.045]) at six months; however, we found a trend towards improvement in overall stigma score and a significant difference in the community discrimination sub-scale among secondary school teachers (mean 3.02 vs. 3.19; adjusted difference, −0.166 [95% CI, −0.310 to −0.022]). ALWH reported few experiences of discrimination, but emphasized keeping their HIV status secret (84%). The teacher-training reduced secondary school teacher perceptions of community-level stigma, but did not impact individual attitudes or beliefs..